Eksistensi Keuangan Kantin Sekolah Pasca Kehadiran Program Makan Bergizi Gratis (MBG) - Silvia Rahmawati; Faza Ilfa; Rauly Sijabat (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The Free Nutritious Meals (MBG) Program is a national policy designed to improve students’ nutritional status and learning capacity. Beyond its social and health objectives, the program also generates economic consequences for school canteens that operate as micro-scale businesses within educational institutions. The implementation of MBG has altered students’ consumption patterns, particularly by reducing reliance on school canteens for main meals. As a result, canteen operators face declining revenues and increased pressure on daily cash flow stability. Using a qualitative descriptive approach, data were obtained through in-depth interviews, non-participant observation, and documentation involving four school canteen managers and two students. The findings indicate a significant decrease in canteen income following the implementation of MBG, primarily due to reduced demand for staple foods. Sales have shifted toward snacks and beverages as complementary consumption. In response, canteen managers adopted adaptive strategies such as reducing inventory, adjusting menus, controlling operational costs, and relying on limited institutional support from schools, including rental fee reductions. The results highlight that school canteens remain economically relevant, although their role has shifted from primary food providers to supplementary service units. Financial sustainability in the post-MBG context depends largely on managerial adaptability, product innovation, and sustained institutional support. These findings contribute to discussions on the unintended economic impacts of public nutrition policies and underscore the importance of integrating micro-business considerations into education-based social programs.